A diplomat and collector: Malcolm MacDonald's pursuit of beauty during the Cold War and end of Empire. (14th November 2017) - Shaw, Alexander Nicholas
Abstract: Malcolm MacDonald was a high-status British diplomat during the period from the 1940s to the 1960s who achieved success through his unconventional, personable approach to international negotiations. He was equally successful as an architect of decolonization in Asia and Africa. At the same time, MacDonald was a collector in a variety of genres. This collecting activity was not separate from his public career as a diplomat and colonial administrator but rather central to it. MacDonald's identity as a collector helped him build relationships with East- and South-East Asian leaders. His views on material culture and enthusiastic patronage of the arts also influenced MacDonald's efforts at cultural decolonization. This article evaluates the links between MacDonald's collecting and his official international duties, arguing that he should be understood as a 'public collector'.